2019
DOI: 10.1101/566752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards an individualised neural assessment of receptive language in children

Abstract: Keywords N400, EEG, language comprehension, sensitivity, Emotiv EPOC+, multivariate pattern analyses Highlights -New methods show hints that brain data can be used to infer language processing -A gaming headset records EEG waveforms comparable to a research grade system -50% of individual children show significant N400 effects in two paradigms -We can decode semantic context in up to 88% of children using multivariate analyses Abstract:Can we use electrophysiological data to assess language processing? Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 67 publications
4
14
0
Order By: Relevance
“…Additionally, studies that do report individual-subject data are often limited by methodological or conceptual factors, such as a lack of proper statistical analyses, or lack of a control group. Recently, two studies have looked at the individual sensitivity of auditory N400 paradigms, in healthy adults (Cruse et al, 2014), and in healthy children (Petit et al, 2019). These studies each used two paradigms contrasting auditory words presented in congruent or incongruent semantic contexts.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, studies that do report individual-subject data are often limited by methodological or conceptual factors, such as a lack of proper statistical analyses, or lack of a control group. Recently, two studies have looked at the individual sensitivity of auditory N400 paradigms, in healthy adults (Cruse et al, 2014), and in healthy children (Petit et al, 2019). These studies each used two paradigms contrasting auditory words presented in congruent or incongruent semantic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…These studies each used two paradigms contrasting auditory words presented in congruent or incongruent semantic contexts. Using a task in which participants were asked to make covert violation decisions, these studies reported a statistically significant N400 effect in a maximum of 58% of neurotypical adults (Cruse et al, 2014) and 56% of neurotypical children (Petit et al, 2019). This moderate sensitivity reflects the challenges associated with assessing ERPs at the individual level.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations